Improving Students’ Critical Thinking to Develop Variety Essays through Picture Word Inductive Model - Rosyada, Amrina (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
Teaching English as a Foreign Language for students in English Education Program sounds less difficult. However, teaching English for Academic Writing that students have to develop their original writings in the form of essays is a great challenge. Most students do not know where to start their writings, how to generate their thoughts, and even how to manage their sentence by sentence in sequence. This study was administered to enhance students’ critical thinking in developing variety essays as the basic writings through Picture Word Inductive Model (PWIM). Engaged by 54 students of English Education Program in sixth semester, the study was measured quantitatively and qualitatively with mix method analysis. The PWIM was applied to inductively generate and improve students’ critical thinking comprised in 2 cycles for two different essay genres which were descriptive essay, and compare and contrast essay. Findings showed that there were 41 students in first cycle and 52 students in second cycle, inductively improved their critical thinking and interestingly experienced new process of writing through the use of PWIM.